Penggusuran Pedagang Kaki Lima Sebagai Perbuatan Melanggar Hukum - Akmal Adicahya (Justitia Jurnal Hukum, 2017)
Mortgage abolishment because the expiration of the Right of Exploitation (HGU) , Right of Building (HGB), and Right of Use burdened not cause the abolishment of collateralized debt obligations. Duration HGU, HGB and wear rights expire, then the mortgage that is charged against the land becomes clear. This additional agreement means clear. Instead principal agreement (credit agreement) is not necessarily to be clear, and move on. In this case resulted in the creditors are in a weak position because of unpaid debts, Mortgage over land as collateral to remove. This study discusses the normative legal efforts to do the lender to avoid the possible risk of the abolishment of land rights based on Law Number 42 Year 1996, which includes the manufacture of promise land extend rights in the imposition of mortgage deed, power of attorney making mortgage charging time HGB changes become ownership rights residential, Object insurance burden for advantage mortgage holder mortgage, debitor to request additional collateral